Investigation of Lightning Flash Locations in Isolated Convection Using LMA Observations. Issue 11 (14th June 2018) - Fuchs, Brody R.; Rutledge, Steven A.
Abstract: Using Lightning Mapping Arrays (LMAs), lightning flash locations in three dimensions have been investigated using multiple methods. Approximately 500, 000 flashes were analyzed to reveal the variability of lightning initiation and propagation within convective storms. These flashes were produced by over 4, 000 isolated convective storms during one warm season across diverse weather regimes in northern Alabama, Washington, D.C., central Oklahoma, and northeastern Colorado. Lightning locations are analyzed within the context of radar reflectivities and examined for vertical variability. Results show that storms in Colorado preferentially produced flashes at lower altitudes and in regions of higher reflectivity compared to the other regions. The regional differences in flash altitudes are largely attributed to the prevalence of anomalous polarity storms (middle‐ or low‐level dominant positive charge) in Colorado, as anomalous storms produced a majority of flashes at lower altitudes compared to storms with normal polarity charge structures (middle‐level negative charge). Conversely, anomalous storms are exceedingly rare in the other regions of study. The differences in flash altitudes are coincident with discrepancies between annual average densities estimated by satellite observations and LMA. Specifically, large differences in annual average flash density estimates exist in northeastern Colorado, which are not present in the other regions, suggesting that the lower altitude flashes in Colorado may be more difficult to detect by satellites. Key Points: Lightning flash locations are investigated using multiple methods and collocated with reflectivity using a large database Anomalously electrified storms in Colorado produced flashes at lower altitudes and in higher radar reflectivities Lightning locations in the vertical may have implications for satellite optical detection and production efficiency of nitrogen oxides and ozone